2018
DOI: 10.1021/acs.est.7b05109
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Illicit Drugs as Biomarkers in Sewers: From Lab to Reality

Abstract: Systematic sampling and analysis of wastewater samples are increasingly adopted for estimating drug consumption in communities. An understanding of the in-sewer transportation and transformation of illicit drug biomarkers is critical for reducing the uncertainty of this evidence-based estimation method. In this study, biomarkers stability was investigated in lab-scale sewer reactors with typical sewer conditions. Kinetic models using the Bayesian statistics method were developed to simulate biomarkers transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(107 citation statements)
references
References 36 publications
8
99
0
Order By: Relevance
“…In‐sewer stability and stability during sampling were not specifically assessed in our study. However, previous works have shown that AE, AEME, BE, and COE have a medium‐to‐high stability in wastewater and, while COC is degraded in a remarkable extension to form BE, the small percentage of excretion of COC in its parent form as compared to the excretion of BE limits the relevance of such transformation in WBE applications.…”
Section: Resultsmentioning
confidence: 99%
“…In‐sewer stability and stability during sampling were not specifically assessed in our study. However, previous works have shown that AE, AEME, BE, and COE have a medium‐to‐high stability in wastewater and, while COC is degraded in a remarkable extension to form BE, the small percentage of excretion of COC in its parent form as compared to the excretion of BE limits the relevance of such transformation in WBE applications.…”
Section: Resultsmentioning
confidence: 99%
“…(h -1 ) represents the processes in the bulk liquid wastewater, mainly μ chemical hydrolysis assuming that the sorption to suspended solids or biofilm is limited for investigated biomarkers 5,14,16,33 and the biological activity of suspended solids is negligible compared to the sewer biofilms or sediments. [34][35][36] It is further postulated that remains the same under aerobic and anaerobic conditions, according to the findings of McCall et al 14 To calibrate the transformation model, experimental datasets obtained from the pilot rising main pipe (Day and 2) and the pilot gravity sewer (Day 4 and 5) pipe were used to estimate and , respectively, through a Bayesian procedure ′ ′ described in Li et al 10 The datasets of Day 3 (rising main) and Day 6 (gravity sewer)…”
Section: Calibration Of Drug Transformation Modelmentioning
confidence: 99%
“…[2][3][4][5] In order to improve the accuracy of back-estimation, researches have been widely conducted to address the uncertainties associated with sampling method and chemical analysis, [5][6][7][8][9] while a comprehensive understanding of biomarkers stability in real sewers is still ongoing. [10][11][12][13][14][15][16][17] Biomarkers are subjected to physiochemical and biological processes during their transport in rising main and gravity sewer pipes, where the hydraulic retention time (HRT) may last for hours. 18 Neglecting the biomarkers transformation (e.g., the degradation or formation in sewers) will lead to an under-or over-estimation of drug consumption in a catchment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, more elaborate sampling campaigns and modelling approaches were published to account for the in-sewer biotransformation of human biomarkers. 15,86,87 Commonly, these studies include selected benchmarking compounds, such as the stable carbamazepine, diclofenac and tramadol and the easily degradable caffeine and acetaminophen, to allow the comparison of biofilm activity between studies. 88 However, the focus of these studies was to assess the suitability of substances as human biomarkers for WBE.…”
Section: Micropollutants In Sewersmentioning
confidence: 99%